Antifungal Test of Telang Flower Ethanol Extract (Clitoria Ternateal) as a Mouthwash Against Candida - Hendri Andrian; Dendy Murdiyanto; Aprilia Yuanita Anwaristi; Nur Ariska Nugrahani (Sean Institute, 2023)
Candidiasis is a disease of the oral cavity caused by fungal changes Candida albicans from sapophytes to pathogens. CI love albicanslive in the human body as saprophytes and can turn into pathogens if there are risk factors such as poor oral hygiene, low immunity, and other factors. So that preventive action can be done by usingmouthwash that can inhibit the growth of bacteria or fungi, one of which is the use of butterfly pea flower extract. Objective: To determine the effectiveness of ethanol flower extract mouthwash in inhibiting growth Candida albicans. Research methods: This research is a true quantitative experimental laboratory test only control group design with a total of 36 samples consisting of positive control, negative control, and basic mouthwash added with 20%, 30%, 40%, and 50% ethanol extract. Research result: There were significant differences between the butterfly pea flower ethanol groups at concentrations of 20%, 30%, 40%, and 50% to the negative control group. So that the ethanol extract of butterfly pea flowers has inhibitory or antifungal power on growth Candida albicans. Conclusion: Mouthwash ethanol extract of butterfly pea flower concentration of 50% is the best concentration in inhibiting growth Candida albicans compared to other groups.